(untitled) (Texas Journal of Engineering and Technology, 2022)
This article is devoted to the regeneration of air filters Mercedes-Benz buses, justified the number of optimal regeneration of clogged air filters. The dynamics of the aerodynamic resistance of air filters is experimentally and theoretically proved, and the second-order polynomials are obtained for the prediction of the change in their resistance by applying the methods of mathematical statistics.